Neuroendoscopic Lavage and Third Ventriculostomy for the Treatment of Intraventricular Hemorrhage and Hydrocephalus in Neonates. A Prospective Study with 18 Months of Follow-Up - Islas-Aguilar, Mario Alberto; Torrez-Corzo, Jaime Gerardo Alberto; Chalita-Williams, Juan Carlos; Cervantes, Dominic Shelby; Vinas-Rios, Juan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Neonatal intraventricular hemorrhage (IVH) may evolve into posthemorrhagic hydrocephalus and cause neurodevelopmental impairment, becoming a common complication of premature infants, occurring in up to 40% of preterm infants weighing less than 1,500 g at birth. Around 10 to 15% of preterm infants develop severe (grades III–IV) IVH. These infants are at high risk of developing posthemorrhagic hydrocephalus. Neuroendoscopic lavage (NEL) is a suitable alternative for the management of this pathology. In this study, an endoscopic surgical approach directed toward the removal of intraventricular hematoma was evaluated for its safety and efficacy.Methods Between August 2016 and December 2019 (29 months), 14 neonates with posthemorrhagic hydrocephalus underwent NEL for removal of intraventricular blood by a single senior neurosurgeon. Complications such as reintervention and ventriculoperitoneal (VP) shunt placement were evaluated prospectively with an 18-month follow-up on average.Results In total, 14 neonates with IVH grades III and IV were prospectively recruited. Of these, six neonates did not need a VP shunt in the follow-up after neuroendoscopy (group 1), whereas eight neonates underwent a VP shunt placement (group 2). Nonsignificant difference between the groups was found concerning days after neuroendoscopy, clot extraction, third ventriculostomy, lamina terminalis fenestration, and septum pellucidum fenestration. In group 2, there was shunt dysfunction in five cases with shunt replacement in four cases.Conclusion NEL is a feasible technique to remove intraventricular blood degradation products and residual hematoma in neonates suffering from posthemorrhagic hydrocephalus. In our series, endoscopic third ventriculostomy (ETV) + NEL could be effective in avoiding hydrocephalus after hemorrhage (no control group studied). Furthermore, patients without the necessity of VP-shunt had a better GMFCS in comparison with shunted patients.
Keywords: neuroendoscopy; intraventricular hemorrhage; neonates